Integration of BIM and GIS: Geometry from IFC to shapefile using open-source technology - Zhu, Junxiang; Wang, Xiangyu; Wang, Peng; Wu, Z.; Kim, M.J. (ELSEVIER SCIENCE BV, 2019)
© 2019 Integration of Building Information Modeling (BIM) and Geographic Information System (GIS) largely relies on data exchange between the two systems. However, the usual tool for geometry transformation from IFC (BIM) to shapefile (GIS), i.e., the Data Interoperability extension for ArcGIS (DIA), tends to result in geometric errors and cause geometric information loss. This study proposes an Open-Source Approach (OSA), in which the geometric information in IFC is retrieved through the spatial structure of IFC, i.e., IFC-Tree, and converted into shapefile by developing an automatic multipatch generation algorithm (AMG). A test on bridge model shows that OSA is more efficient than DIA and is comparable to Feature Manipulation Engine (FME), and the transformed model is easier to manage and can be used in more applications. OSA can link BIM and GIS in a more stable and efficient manner by enhancing the data transformation from BIM to GIS. However, its efficiency should be further improved compared with FME.